EFFICIENCY OF EARTHWORM, Eudrilus eugeniae TO DECOMPOSE ORGANIC WASTE - Chaichana, Rapeeporn (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The comparison of bedding material ratio for feeding Eudrilus eugeniae was studied. The experiment was designed with Complete Randomized Design (CRD) consisted of 4 treatments as follow: 1) control (cow dung: coconut husk (2:1 w/w), 2) cow dung: kale (2:1 w/w), 3) cow dung: coconut husk: kale (2: 0.5: 0.5 w/w) and 4) cow dung: coconut husk: kale (2:1:0.5 w/w). The experiment was operated for 50 days and the results indicated that treatment 3 gave the highest total nitrogen, phosphorus, potassium and pH at 2.31%, 0.89%, 1.50% and 6.55% (P < 0.05), respectively. Treatment 2 gave the highest percentage of organic carbon (OC), organic matter (OM) and C:N ratio at 28.67%, 49.32%, and 17%, respectively. Meanwhile, treatment 4 showed the highest electrical conductivity (EC) at 4.95 (dS/m) (P < 0.05). From all of the results, it was clearly that vermicompost produced from this study provided the better quality of fertilizer than the organic fertilizer standard. However, treatment 1 gave the higher vermicompost yield than other groups (P < 0.05).